Drgania Pewnego Nieliniowego Układu o Zmiennej Sztywności - Osiński, Z. (Engineering Transactions, 1967)
The object of the present investigation is longitudinal vibration of a mass suspended on a steel rope with nonlinear characteristic taking into consideration monotonous motion of the rope. This motion causes variability of the active length of the rope. The solution is obtained by means of the Kryloff-Bogoluboff method adapted for the investigation of nonlinear vibrations with slowly varying parameters. The influence of the motion of the rope on the amplitude and frequency of vibration is analysed.